2007
DOI: 10.1007/s00262-007-0412-2
|View full text |Cite
|
Sign up to set email alerts
|

Soluble factors released by activated cytotoxic T lymphocytes interfere with death receptor pathways in neuroblastoma

Abstract: Neuroblastoma (NB) is often described as an unfavorable target for both HLA-restricted and death receptor-mediated elimination by cytotoxic T lymphocytes (CTLs) due to low or absent HLA class I and caspase-8 expression. We investigated the effects of soluble factors released by CTLs activated by TCR triggering (named as activated supernatant; AS) on the levels and composition of cell surface molecules involved in HLA-restricted and HLA-independent NB cell recognition (surface immune phenotype). Using a panel o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 656 publications
(782 reference statements)
0
4
0
Order By: Relevance
“…ImmTAC-activated T cells release soluble factors including interferon-γ, IL-2 and TNFα (Fig. 1b), which can not only attract additional T cells and other effector immune cells to the tumor site but also promote components of the death receptor pathway in the tumor cells [52], which can result in long-term anti-tumor activity. In cancer patients, it is probable that mechanisms such as epitope spreading (activation of endogenous T cells specific for other tumor epitopes) will occur, following cross-presentation of antigens from lysed tumor cells by dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…ImmTAC-activated T cells release soluble factors including interferon-γ, IL-2 and TNFα (Fig. 1b), which can not only attract additional T cells and other effector immune cells to the tumor site but also promote components of the death receptor pathway in the tumor cells [52], which can result in long-term anti-tumor activity. In cancer patients, it is probable that mechanisms such as epitope spreading (activation of endogenous T cells specific for other tumor epitopes) will occur, following cross-presentation of antigens from lysed tumor cells by dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, activated T cells can kill NB cells in an MHC-unrestricted fashion. We have previously shown that (1) activated cytotoxic T lymphocytes (CTLs) can induce the MHC-independent demise of NB cells not only in a caspase-dependent but also in a caspase-independent manner 4 and that (2) soluble factors released by activated CTLs sensitize NB cells to death receptor-mediated killing by T cells 5 . The latter observation is of special importance since the epigenetic silencing of caspase-8 has frequently been observed in NB cells (reviewed in ref.…”
Section: Introductionmentioning
confidence: 99%
“…ImmTAC-NYE was able to bind to cells with a lowdensity of HLA-A2/peptide complexes, suggesting maintained functionality despite MHC down-regulation. The study also found that ImmTAC-NYE-activated T cells release cytokines IFN-γ, IL-2, and TNF-α, which, in addition to attracting effector immune cells to the tumor site, may spur long-term anti-tumor activity by promoting components of the death receptor pathway in tumor cells, providing an additional mechanism of tumor cell killing even after the BsAb is metabolized (89,216).…”
Section: Preclinical Models Of Ny-eso-1-targeting Bsabs Immtac-nyementioning
confidence: 83%